Design and Validation of a Low-Cost, Portable Arduino-Based Platform for Assessing Physicochemical Drinking Water Quality Across Urban and Peri-urban Areas of Delhi and Surrounding Regions - Singh, Arjun; Arya, Rahul; Choudhary, Nikki; Poudel, Navraj; Arora, Poonam; Maurya, K. K.; Mandal, T. K.; Sharma, S. K.; Kumar, Prashant; Pathak, Saurabh; Pant, R. P. (Water conservation science and engineering, 2025)
This study presents the design, development, and pilot-scale validation of a low-cost, Arduino-based sensor platform for on-site monitoring of drinking water quality across Delhi’s National Capital Region (NCR) and surrounding areas. A total of 47 water samples, selected through a pilot-scale design aimed at diverse geographic and supply type representation, were collected from public sources (municipal supply, reverse osmosis (RO)-treated, and groundwater), and six commercial bottled water samples were collected and analysed in July 2023 using standardized protocols. The system was built around an Arduino UNO with an ATmega328 microcontroller, interfaced with calibrated sensors for pH (ERMA Inc., PE-03, ± 0.01), TDS (Techtonics, 0–1000 ppm), turbidity (analogue module, Robocraze-distributed, 0–100 NTU), and temperature (DS18B20, ± 0.5 °C). Data were recorded at 1 Hz sampling frequency with an overall accuracy within ± 5%, validated against NIST-traceable reference standards. The system effectively measured a broad range of field conditions, including pH (6.5–8.6), TDS (5–774 mg/L), turbidity (0–3 NTU), and temperature (25.8–31 °C). Results demonstrated strong agreement with national Bureau of Indian Standards (BIS) standards, with most samples falling within the desirable limits. RO-treated and bottled water samples showed consistently stable readings, while the system successfully captured variations across municipal and groundwater sources—demonstrating its sensitivity, repeatability, and practical utility for real-world deployment. Designed with modular architecture and USB-based data logging, the platform is scalable, portable, and adaptable for future integration with wireless transmission modules (e.g., GSM, Wi-Fi). While this prototype focused on physicochemical parameters, future iterations will incorporate microbial and heavy metal sensors, as well as time-series data logging for continuous monitoring. This pilot project demonstrates the technical feasibility and measurement reliability of a cost-effective, sensor-driven approach to urban water monitoring. An expanded, multi-parameter study covering broader geographic and temporal scales will follow in the next phase.